Optimization of Distributed ADMM Algorithm Based on Minimum Network Latency - Zeng, Shuai; Wang, Shuangsheng; Zhang, Yi (Proceedings of the International Symposium on Computational Intelligence and Design, 2019)
In order to solve the problem that the running speed of distributed ADMM algorithm is limited by the nodes with large network latency, a master node selection policy is proposed, which is based on the communication delay between network nodes, and the policy aims to reduce the running time of distributed ADMM algorithm in the connected network. Experiment results show that the policy can effectively reduce the running time of distributed ADMM algorithm in connected networks, and the calculation accuracy is not affected. And the smaller the connection probability between network nodes, the more significant the advantages of the proposed policy are. And when there is a communication failure between a few nodes in the connected network, the strategy proposed in this paper is not affected much.